Effect of veneering materials on fracture loads of implant-supported zirconia molar fixed dental prostheses. Issue 2 (April 2019) - Kondo, Tomohide; Komine, Futoshi; Honda, Junichi; Takata, Hiroki; Moriya, Yuta
Abstract: Purpose: To determine the effect of veneering material and framework design on fracture loads of implant-supported zirconia molar fixed dental prostheses (FDPs). Methods: Sixty-six zirconia FDPs were manufactured onto two implants and classified as uniform thickness (UT) or anatomic design (AD). These framework design groups were then further divided into three subgroups ( n  = 11): feldspathic porcelain-veneered zirconia FDPs (PVZ), indirect composite-veneered zirconia FDPs (IVZ), and metal–ceramic FDPs (MC). The FDPs were luted on the implant abutments and underwent fracture load testing. Significant differences were assessed by the Kruskal–Wallis test and Mann–Whitney U -test ( α  = 0.05). Results: For UT group, median fracture load was significantly higher for the IVZ (1.87 kN) and MC (1.90 kN) specimens than for the PVZ specimens (1.38 kN) ( p <  0.05). In the AD group, the IVZ specimens had the highest median fracture load (4.10 kN) of the three groups tested. The AD group exhibited higher median fracture loads than the UT group in all subgroups. Conclusions: Indirect composite appears to be a useful alternative to feldspathic porcelain as the layering material for implant-supported zirconia FDPs. The AD group had higher fracture loads than UT group. In addition, implant-supported indirect composite-veneered zirconia-based FDPs appear to be clinically feasible.